2020
DOI: 10.3390/ijms21228563
|View full text |Cite
|
Sign up to set email alerts
|

A New Twist in Protein Kinase B/Akt Signaling: Role of Altered Cancer Cell Metabolism in Akt-Mediated Therapy Resistance

Abstract: Cancer resistance to chemotherapy, radiotherapy and molecular-targeted agents is a major obstacle to successful cancer therapy. Herein, aberrant activation of the phosphatidyl-inositol-3-kinase (PI3K)/protein kinase B (Akt) pathway is one of the most frequently deregulated pathways in cancer cells and has been associated with multiple aspects of therapy resistance. These include, for example, survival under stress conditions, apoptosis resistance, activation of the cellular response to DNA damage and repair of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 262 publications
(271 reference statements)
0
25
0
Order By: Relevance
“…DNA repair demands high energy inputs, which potentially links cancer cell metabolism and resistance to irradiation ( Götting et al., 2020 ; Rashmi et al., 2018 ; Tang et al., 2018 ; Turgeon et al., 2018 ). The genetic and metabolic capacity of cells to repair radiation-induced lethal DNA lesions with high efficiency is considered as one critical determinant of radiation resistance ( Mladenov et al., 2013 ; Roos et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…DNA repair demands high energy inputs, which potentially links cancer cell metabolism and resistance to irradiation ( Götting et al., 2020 ; Rashmi et al., 2018 ; Tang et al., 2018 ; Turgeon et al., 2018 ). The genetic and metabolic capacity of cells to repair radiation-induced lethal DNA lesions with high efficiency is considered as one critical determinant of radiation resistance ( Mladenov et al., 2013 ; Roos et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The PI3K/Akt signaling pathway plays an important role in regulating various cell functions, including metabolism, growth, proliferation, survival, transcription, and protein synthesis (Li et al, 2019). Aberrant activation of the PI3K/Akt pathway is one of the most frequently deregulated pathways in cancer cells (Gotting et al, 2020). Research by Yan Mei et al identified distinct patterns of oncogenic pathways activation at different stages of breast cancer and uncovered five oncogenic pathways that were activated in both human and mouse breast cancers, including PI3K/Akt signaling pathway (Mei et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…There are increasing data about metabolic rewiring and alterations in cellular metabolism after different chemotherapeutic treatments. It has been observed that the administered treatments could modulate cellular mechanisms, including alterations in the activation of autophagy, oxidative phosphorylation (OXPHOS) or Warburg reverse Warburg effects cell type and treatment dependently [ 40 , 41 ]. For instance, doxorubicin causes DNA damage and related apoptosis; simultaneously, it has metabolism-interfering effects.…”
Section: Discussionmentioning
confidence: 99%